Depression in gestants and the support of the couple - Solís-Rojas, Mirian (2019)
Objective. Decide the association between the support of the couple and depression in pregnant women of the third trimester of pregnancy attending to the National Maternal and Perinatal Institute in the months of June and July of 2017. Methodology. Observational, analytical study of cases and controls, prospective and cross-sectional, in which there were two groups: 45 pregnant women with depression (case group) and 45 pregnant women without depression (control group), who met the selection criteria. The inferential statistic was used by Pearson's chi-squared test (X2), which was considered significant when the value of p is less than 0,05. Results. It was found association between emotional support (p = 0,000), instrumental support (p = 0,001), informational support (p = 0,000) and evaluative support (p = 0,000) with the presence of depression in pregnant women. At a general level, lack of support from the couple was associated with the presence of depression in pregnant women (p = 0,000), increased the risk of presentation 7 times (OR: 7,61). Conclusion. There is a significant association between the support of the couple and the depression in pregnant women of the third trimester of pregnancy attending to the National Maternal and Perinatal Institute in the months of June and July of 2017 (p=0,000).